Lecturers’ Perception on Tasks and Operations Expected for 30-39 Assessment of Agricultural Practical’s in Colleges of Education in Adamawa and Taraba States, Nigeria - Musa, I. G.; Harrison, G. M (Kashere Journal of Education, 2021)
The study was carried out to determine lecturers’ perception on tasks and operations expected for the assessment of agricultural practical in Colleges of Education in Adamawa and Taraba States, Nigeria. Three research questions and two null hypotheses were formulated to guide the study; the hypotheses were tested at 0.05 level of significance. The population of this study was 50 agriculture education lecturers teaching practical agriculture in Colleges of Education in Adamawa and Taraba States, sample and sampling techniques were not used in the study because the entire population was manageable and used for the study. Data were collected using a researcher designed instruments titled Instrument for Assessing Students’ Skills in Agriculture Practical (IASSAP), Expected Tasks and Operations for Agricultural Practical (ETOAP) and Observable Skills Assessed by Lecturers during Agricultural Practical (OSALAP). Mean was used to answer the research questions while z-test was used to test the hypotheses. The findings of this study revealed that 26 tasks and operations were identified as expected tasks and operations to be carried out by the students during agricultural practical on the field. The hypotheses tested revealed that there is no significance difference in the means rating of the lecturers in Federal and State Colleges of Education on observable skills and expected tasks and operations appropriate for assessing agriculture practical in the Colleges of Education. It was recommended that when assessing practical skills lecturers should use appropriate, comprehensive and objective instrument that contains the tasks and operations expected to be performed by the students of agriculture during the process of carrying out agriculture practical. Keywords: Task, Assessment, Practical Agriculture and Colleges of Education